THE ROLE OF MOVIES AND TV SERIES IN IMPROVING LISTENING AND VOCABULARY SKILLS - Odilova Zuhrakhon, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This  research  investigates  the  role  of  movies  and  TV  series  in  enhancing vocabulary acquisition and listening skills through the lens of cognitive load theory. The  paper  analyzes  the  efficacy  of  subtitle  usage  in  the  retention  of  idiomatic expressions. Findings emphasize that audio-visual integration significantly improves long-term  memory  recall  and  phonological  loop  development  in  foreign  language acquisition. By examining the intersection of entertainment and education, this study highlights how cinematography serves as a "multi-modal" bridge for L2 learners.